Climate change versus winter sports; can athlete climate activism change the score? - Knowles, N. L.; Scott, D.; Rutty, M. (International Review for the Sociology of Sport, 2024)
Outdoor winter sports sit on the frontlines of climate change, with athletes subject to increasingly unsafe, unfair and non-ideal competition and training conditions as a result. With athletes` livelihoods and the future of winter sports on the line, this research investigates if and how winter athletes use their position as public figures, celebrities and role models to challenge the hegemonic structures in sports and society driving climate change. Framed through the broad athlete-activism literature, this study used a qualitative survey of 390 elite winter-sport athletes and coaches combined with eight key stakeholder interviews to understand athlete climate activism. Results demonstrate that winter athletes` climate action is generally low risk constituting advocacy rather than activism. Athletes express fear of being called out as hypocritical for their high-carbon sport and lifestyle, insecurity over their level of climate education and frustration with the lack of climate action from international- and national-level winter-sport organizations. Scholarly, grassroots and sport-based activism may help athletes engage more effectively in climate activism within and beyond sport.